Well-differentiated systemic mastocytosis showed excellent clinical response to imatinib in the absence of known molecular genetic abnormalities: A case report. Issue 41 (October 2016) - Huang, Lanshan; Wang, Sa A.; Konoplev, Sergej; Bueso-Ramos, Carlos E.; Thakral, Beenu; Miranda, Roberto N.; Jabbour, Elias; Medeiros, L. Jeffrey; Kanagal-Shamanna, Rashmi
Abstract: Introduction: Well-differentiated systemic mastocytosis (WDSM) is a rare, recently recognized provisional subvariant of systemic mastocytosis (SM). We report a case of WDSM that showed excellent clinical and cutaneous response to imatinib in the absence of known molecular genetic abnormalities. Clinical Findings/Diagnoses: We present a 24-year-old woman with childhood onset of skin manifestations that progressed to mediator-related systemic events, and a gastrointestinal tract mastocytoma. A subsequent bone marrow examination showed WDSM. Treatment with imatinib resulted in complete resolution of cutaneous lesions and systemic symptoms, which relapsed with the discontinuation of the drug. Targeted next-generation sequencing-based mutation analysis did not demonstrate any mutations in the coding regions of KIT or other genes commonly associated with myeloid neoplasms. Conclusions: The diagnosis of WDSM is challenging in the absence of spindle-shaped mast cells, CD2 or CD25 expression, and KIT D816 mutation. This case illustrated the need for recognizing this unique variant of SM for diagnostic and therapeutic implications.